The effects of eco-tourism on rural land transformation in Mapungubwe National Park, Limpopo Province, South Africa - Makwela, Sethepele Elizabeth (My University, 2022)
Globally, eco-tourism has been recognised as a tool to enhance rural land transformation, mostly in areas and around eco-tourism destinations or those rich with natural resources. With that, literature has confirmed that there is a well-established principle between eco-tourism and rural land transformation in most countries across the globe. Theoretically, the establishments and expansion of eco-tourism do not necessarily bring only rural land transformation and associated benefits to the society but also entail various challenges. The challenges are inclusive of but not limited to threats to indigenous cultures and environmental degradation. Thus, this study was designed and undertaken to explore the effects of eco-tourism on rural land transformation in Mapungubwe National Park. The study utilised both qualitative and quantitative research methods and both qualitative and qualitative data was collected theoretically and empirically on the effects of eco-tourism on rural land transformation. Data collection techniques included semi-structured questionnaires with a sample size of 43 respondents, interview schedules for 8 respondents and observations. Recordings of the interviews with the participants were transcribed and analysed including the findings which emanated from this investigation. The findings reveal that eco-tourism does play an important part in ensuring improvement of the Musina local municipal area’s economy, where the Mapungubwe National Park is located. However, there still seems to be lot that needs to be done to ensure eco-tourism is sustainable to ensure there is rural land transformation and economic growth by eliminating damage to the natural ecosystems. Economic growth is always affected by the changing environments, either negatively or positively and there, the concept always comes in where tourism is concerned. The minimal positive impact it was making is improving some people’s lives and through job creation (South African National Parks, 2006). The study revealed that eco-tourism does have positive effect on rural land transformation in the Mapungubwe National Park, which include economic growth through tourist attraction. The researcher is of the view that ecotourism is playing significant role in the rural land transformation of Mapungubwe National Park.
Thesis (M.Dev. (Planning and Management)) -- University of Limpopo, 2022
Keywords: Eco-tourism; Rural land transformation; Ecotourism; Land use, Rural -- South Africa